FENOMENOLOGI HUSSERL DALAM PENELITIAN LINGKUNGAN BINAAN-PERILAKU MANUSIA - Yudi Waani (EKOTON, 2014)
Failures in planning and design of the built environment and especially on aristektur and settlements and cities, as many who saw the vision of science in terms of physical space and numbers. This understanding comes from a positivistic paradigm to a separation between subject and object. The need for understanding the phenomenology paradigm to find meaning and value of society itself. Therefore, research on humans and their activities in view of space as the built environment is to understand existing local knowledge in local communities. Local knowledge is part of the community culture into the community foothold in thinking, acting and then form the built environment.